An assessment of perioperative respiratory adverse events and difficult intubation in pediatric patients with Trisomy 21. Issue 4 (24th February 2021) - Graber, Taylor J.; Baskin, Paola Lopomo; Soria, Claire; Greenberg, Mark; Gabriel, Rodney A.; Brzenski, Alyssa
Abstract: Introduction: Several prior studies have demonstrated an association between trisomy 21 and airway‐related anesthetic complications. However, there is a paucity of large clinical studies characterizing the airway challenges associated with trisomy 21. In this analysis, we examine anesthetic‐related airway complications in children with trisomy 21 and compare our findings to well‐matched controls. Methods: A chart review of all general anesthetics occurring between 2011 and 2017 at a single pediatric hospital was performed. Children with trisomy 21 were identified. Matched controls were created using a 1:1 propensity score and controlling for patient sex, patient age, surgical specialty, airway management, and anesthetic induction technique. The primary outcomes were the numbers of difficult intubations and perioperative respiratory adverse events. Secondary outcomes included the number of intubation attempts and the Cormack‐Lehane grade in each cohort. Results/Data analysis: A total of 2702 anesthetic records were reviewed. Propensity score matching resulted in adequately matched control groups as indicated by a standard mean difference below 0.2 in each case. Logistic regression analysis between trisomy 21 patients and matched controls demonstrated that the trisomy 21 cohort had a higher incidence of perioperative respiratory adverse events (OR 2.04, 95% CI 1.34–3.09, p = .0008) due largely to a higher incidence of airway obstruction (1.7% vs. 0.2%, p = .0005). The trisomy 21 group had a lower rate of difficult intubation (OR 0.26, 95% CI 0.07–0.91, p = .034). There was no association between trisomy 21 and the number of intubation attempts (RR 0.99, 95% CI 0.88–1.13, p = .92) or Cormack‐Lehane grade (RR 0.95, 95% CI 0.87–1.05, p = .35). Discussion: The trisomy 21 cohort had an increased incidence of perioperative respiratory adverse events compared to matched controls, largely secondary to a higher rate of obstructed ventilation, but without statistically different rates of laryngospasm, bronchospasm, postextubation stridor, or other desaturation events. Our trisomy 21 cohort had a decreased incidence of difficult intubation. There was no association between trisomy 21 and number of attempts required to successfully place an endotracheal tube or a less favorable CL grade. Conclusions: Compared to matched controls, children with trisomy 21 have a lower incidence of difficult intubation and a higher incidence of perioperative respiratory adverse events, largely due to increased rate of airway obstruction.